Alpha-v–containing integrins are host receptors for the Plasmodium falciparum sporozoite surface protein, TRAP - Dundas, Kirsten (Proc Natl Acad Sci U S A, 2018)
Malaria-causing Plasmodium sporozoites are deposited in the dermis by the bite of an infected mosquito and move by gliding motility to the liver where they invade and develop within host hepatocytes. Although extracellular interactions between Plasmodium sporozoite ligands and host receptors provide important guidance cues for productive infection and are good vaccine targets, these interactions remain largely uncharacterized. Thrombospondin-related anonymous protein (TRAP) is a parasite cell surface ligand that is essential for both gliding motility and invasion because it couples the extracellular binding of host receptors to the parasite cytoplasmic actinomyosin motor; however, the molecular nature of the host TRAP receptors is poorly defined. Here, we use a systematic extracellular protein interaction screening approach to identify the integrin αvβ3 as a directly interacting host receptor for Plasmodium falciparum TRAP. Biochemical characterization of the interaction suggests a two-site binding model, requiring contributions from both the von Willebrand factor A domain and the RGD motif of TRAP for integrin binding. We show that TRAP binding to cells is promoted in the presence of integrin-activating proadhesive Mn(2+) ions, and that cells genetically targeted so that they lack cell surface expression of the integrin αv-subunit are no longer able to bind TRAP. P. falciparum sporozoites moved with greater speed in the dermis of Itgb3-deficient mice, suggesting that the interaction has a role in sporozoite migration. The identification of the integrin αvβ3 as the host receptor for TRAP provides an important demonstration of a sporozoite surface ligand that directly interacts with host receptors.